Interdisziplinäre Anforderungen für die Implementierung eines innovativen Konzeptes zur stationären ALS-Versorgung in einem Maximalversorgerkrankenhaus : eine qualitative Studie - Leonie Fischer (2023)
Amyotrophic lateral sclerosis (ALS) is a progressive, degenerative motor neuron disease associated with significant loss of mobility and limitations in speech, swallowing, and breathing. As there is currently no cure for ALS, the focus is on symptomatic treatment of the patients. Studies have shown that a multi- and interdisciplinary approach to the treatment and care of ALS patients increases their quality of life. Despite existing evidence on the effectiveness of multi- and interdisciplinarity in this context, there are hardly any practical implementations of such extended care concepts in the stationary setting so far. Within the framework of two focus group interviews, differently composed, multiprofessional teams of the neurological and intensive care wards at the University Medical Center Eppendorf (UKE) were questioned about the establishment of an innovative care concept for the interdisciplinary treatment of ALS patients. Within the two focus group interviews, two participants from the profession of health care and nursing as well as one participant each from occupational therapy, speech therapy and physiotherapy were interviewed. The conversations were conducted as a semi-structured interview with six open-ended questions by the author, digitally recorded, and subsequently transcribed. The transcripts were pseudonymized and subsequently analyzed via deductive categorization of the results using qualitative data analysis according to Mayring. It has become clear that the majority of the interviewed participants perceive the current nursing and therapeutic care structure at the UKE as good and in parts interdisciplinary. Deficits are particularly evident in the interdisciplinary nature of intensive care nursing as well as in the subareas of psychological care and the provision of medical aids. Regarding the future care situation, optimization proposals for this as well as the embedding of these in an adapted concept via an ALS consilience team are described. The results of the surveys on the current care situation are reflected in the literature. From the results, interdisciplinary requirements for the implementation of an innovative care concept can be derived, which allow a successive establishment of the ALS consilience team.
Keywords: Amyotrophic lateral sclerosis (ALS); multidisciplinarity; interdisciplinarity; innovative care concept